THE MEANING OF BEAUTY IN PHENOMONOLOGICAL PERSPECTIVE AMONG STUDENTS OF UNIVERSITAS NEGERI MAKASSAR - Sadriani, Andi; Darmayanti, Dyan Paramitha; Warda, Syarifah Wafiqah (Social Landscape Journal, 2023)
This article reviews how students of the Faculty of Social Sciences, Makassar State University, class of 2021 interpret the concept of beauty. This study arises because the author wants to understand how the meaning of beauty among students, considering that the author's findings from initial observations indicate variations in perception in understanding the concept of beauty. This difference tends to be related to appearance, so students try to look attractive by using makeup when going to campus. This shows that the concept of beauty has become a necessity that seeks social recognition, appreciation, and self-achievement among students. This research uses Alfred Schutz's Phenomenological theory in a qualitative research approach with a phenomenological type of study. The results showed that each student has a different perception of beauty in their appearance when on campus. They tend to focus more on objective aspects of understanding beauty, such as white skin, attractive appearance, face, attitude, and behavior, rather than subjective aspects related to the heart, soul, and positive thinking. Students who want to look beautiful tend to assume that by putting on makeup and following beauty trends, they will be more accepted in their social environment.